Primary Syphilis in the Male Urethra: A Case Report. (10th September 2018) - Chambers, Laura C; Srinivasan, Sujatha; Lukehart, Sheila A; Ocbamichael, Negusse; Morgan, Jennifer L; Lowens, M Sylvan; Fredricks, David N; Golden, Matthew R; Manhart, Lisa E
Abstract: We documented urethral Treponema pallidum infection in a man with nongonococcal urethritis and a negative syphilis serology using broad-range bacterial polymerase chain reaction (PCR) and sequencing, targeted PCR, and immunofluorescence microscopy. He subsequently seroconverted for syphilis. Early syphilis may present as urethritis. Urethral T. pallidum shedding can occur before seroconversion.